Corporate culture and the performance of those listed companies on KLSE within consumer product sector / Isham Shol Hashim - Hashim, Isham Shol (1995)
The study focused on the corporate culture and the performance of those listed companies on KLSE within consumer product sector. The primary question of this study is whether the corporate culture has any impact or useful in enhancing the companies' performance. This paper presents a literature review of studies carried out by western researchers on corporate culture with the main focus is the elements of corporate culture. Due to the fact that there are seven main elements of corporate culture which are leadership style, total quality management, innovative ideas, empowerment, employee morale, leadership quality and teamwork. All the companies' data relating to corporate culture were obtained through questionnaire that were send personally to the Human Resource Manager or the Officer. To test whether is there any significant relationship between corporate culture and the companies' performance, the data gathered that consist of seven corporate culture elements were regressed individually against performance indicator. The indicators are net income growth index, average annual return on capital, average annual growth of stock price and constant growth of stock price. The SPSS processor was capitalize on in this test. Evidence in United States showed that there is direct relationship between corporate culture and corporate performance. It is believed that the strong culture within an organization, they are likely to perform more successfully than if they do not have the culture. Therefore this study tried to find out whether corporate culture will also enhance the performance of those listed companies on ELSE within consumer product sector. The empirical finding of this of this study showed contradictory result. There is no significant relationship at all between corporate culture and companies' performance. In other words, corporate culture has no influence on the performance of those companies. This study also found that the corporate culture in this particular sector is relatively high but it somehow did not contribute to enhance the performance of those companies.